MLIF Modulates Microglia Polarization in Ischemic Stroke by Targeting eEF1A1 - Liu, Yulan; Deng, Shanshan; Song, Zhibing; Zhang, Qian; Guo, Yuchen; Yu, Yongsheng; Wang, Yuliang; Li, Tiejun; Megahed, Fayed A. K.; Addissouky, Tamer A.; Mao, Junqin; Zhang, Yuefan (Frontiers in Pharmacology, 2021)
Monocyte locomotion inhibitory factor (MLIF) is a heat-stable pentapeptide from Entamoeba histolytica. Our previous study found that MLIF protects against ischemic stroke in rats and mice, and exerts neuroprotection effect in human neuroblastoma SH-SY5Y cells. Microglia/macrophage polarization has been proven to be vital in the pathology of ischemic stroke. Nevertheless, whether MLIF is able to modulate microglia/macrophage polarization remains unclear. We performed middle cerebral artery occlusion (MCAO) on C57BL/6J male mice and induced cultured BV2 microglia by oxygen-glucose deprivation (OGD), respectively. Immunﬂuorescence was utilized to detect the M1/2 marker, such as CD206 and CD16/32. qPCR and ELISA were used to detect the signature gene change of M1/2. The MAPK and NF-κB pathway associated proteins were measured by western blot. To identify the protein target of MLIF, a pull-down assay was performed. We found MLIF promoted microglia transferring from a “sick” M1 phenotype to a “healthy” M2 phenotype in vivo or in vitro. Furthermore, we proved that eukaryotic elongation factor1A1 (eEF1A1) was involved in the modulation of microglia/macrophage polarization. Knocking down eEF1A1 by siRNA exhibited the M1 promotion effect and M2 inhibition effect. Taken together, our results demonstrated that MLIF modulated microglia/macrophage polarization by targeting eEF1A1 in ischemic stroke.